Potential of integrated field spectroscopy and spatial analysis for enhanced assessment of soil contamination: A prospective review - Horta, A.; Malone, B.; Stockmann, U.; Minasny, B.; Bishop, T.F.A.; McBratney, A.B.; Pallasser, R.; Pozza, L. (Geoderma, 2015)
There are tens of millions of contaminated soil sites in the world, and with an increasing population and associated risk there is a growing pressure to remediate them. A barrier to remediation is the lack of cost-effective approaches to assessment. Soil contaminants include a wide range of natural and synthetic metallic and organic compounds and minerals thus making analytical costs potentially very large. Further, soil contaminants show a large degree of spatial variation which increases the burden on sampling costs. This paper reviews potentially cost-effective methods for measurement, sampling design, and assessment. Current tiered investigation approaches and sampling strategies can be improved by using new technologies such as proximal sensing. Design of sampling can be aided by on-the-go proximal soil sensing; and expedited by subsequent adaptive spatially optimal sampling and prediction procedures enabled by field spectroscopic methods and advanced geostatistics. Field deployment of portable Visible & Near Infrared [wavelength 400–2500nm] (Vis-NIR) and X-ray fluorescence (PXRF) spectroscopies will require special calibration approaches but show huge potential for synergistic use. The use of mid-infrared spectroscopy [wavelength 2500–25,000nm, wavenumber 4000–400cm−1] (MIR) for field implementation requires further adaptive research. We propose an integrated field-deployable methodology as a basis for further developments. •There is still a large number of contaminated soil sites worldwide.•Lab analysis of soil contaminants increases investigation and remediation costs.•Field-deployable portable instruments for Vis-NIR and PXRF are now widely available.•A new approach includes adaptive sampling supported by on-the-go Vis-NIR and PXRF.